Chemical Synthesis in Solution and Porphyrin Nanostructures on Surfaces - Similar Concepts, Different Results. - RYAN, AOIFE; SENGE, MATHIAS (My University, 2013)
The chemistry of porphyrins is reaching out to more complex and ever larger polyporphyrin arrays. In solution the synthesis of porphyrin arrays is greatly aided by recent advances in organometallic chemistry which now allows the rational construction of selected tetrapyrrole scaffolds. Examples for these are unsymmetrical porphyrin arrays with conjugating and nonconjugating linker groups and the use of presenting scaffolds such as triptycenes. In order to circumvent a laborious and stepwise organic synthesis of porphyrin arrays efforts are underway to utilize principles of self-aggregation and organization for the construction of ordered nanostructural arrays on metal surfaces. Here, even rather simple systems are able to form highly ordered structures. On the other hand, thermal activation can be used to form covalent bonds between individual porphyrin molecules to yield highly ordered, large, and stable arrays. The type of structures formed depends on the porphyrinoid material, the metal surface, and the deposition methods.
PUBLISHED
Keywords: porphyrins; Nanoscience & Materials